Technological Functionalisation of Microencapsulated Genistein and Daidzein Delivery Systems Soluble in the Stomach and Intestines - Jurga Andreja Kazlauskaite; Inga Matulyte; Mindaugas Marksa; Jurga Bernatoniene (MDPI AG, 2024)
Encapsulating antioxidant-rich plant extracts, such as those found in red clover, within microcapsules helps protect them from degradation, thus improving stability, shelf life, and effectiveness. This study aimed to develop a microencapsulation delivery system using chitosan and alginate for microcapsules that dissolve in both the stomach and intestines, with the use of natural and synthetic emulsifiers. The microcapsules were formed using the extrusion method and employing alginate or chitosan as shell-forming material. In this study, all selected emulsifiers formed Pickering (β-CD) and traditional (white mustard extract, polysorbate 80) stable emulsions. Alginate-based emulsions resulted in microemulsions, while chitosan-based emulsions formed macroemulsions, distinguishable by oil droplet size. Although chitosan formulations with higher red clover extract (C1) concentrations showed potential, they exhibited slightly reduced firmness compared to other formulations (C2). Additionally, both alginate and chitosan formulations containing β-CD released bioactive compounds more effectively. The combined use of alginate and chitosan microcapsules in a single pill offers an innovative way to ensure dual solubility in both stomach and intestinal environments, increasing versatility for biomedical and pharmaceutical applications.